Centroid variability model–based control of HITUWV for automatic underwater welding with enhanced stability and accuracy. (November 2019) - Luo, Yang; Tao, Jianguo; Hao, Zhuang; Sun, Hao; Li, Zhandong; Gao, Haibo; Ding, Liang; Deng, Zongquan
This article presents a centroid variability model–based controller of HITUWV (Underwater Welding Vehicle by Harbin Institute of Technology), an underwater welding vehicle, for automatic welding with high stability and accuracy. First, an accurate centroid variability model, which considers the coefficient changes of the HITUWV caused by the movements of a 3-degree-of-freedom manipulator, is presented to perform the dynamic characteristics of the HITUWV precisely. Second, a centroid variability model–based adaptive sliding model controller is developed for the HITUWV to complete centroid variability compensation. Experimental results indicate that the proposed centroid variability model–based adaptive sliding model controller demonstrates better performances in stability and accuracy than the conventional proportional–integral–derivative controller and the model-based proportional–integral–derivative controller. As a result, the centroid variability model–based adaptive sliding model controller holds great practicality and utility on the control of underwater operation with high stability and accuracy.